FACTORS THAT RELEVANT TO THE QUALITY OF LIFE OF BREAST CANCER PATIENTS - Haris H; Laili Rahayuwati; Ahmad Yamin (Journal of Maternity Care and Reproductive Health, 2018)
Breast cancer is a health problem since so many years ago especially to women. In 2013, Basic Health Research (Riskesdas) showed that the number of national breast cancer prevalence was the second most numerous patients in the world especially attacked women in Indonesia. The common problems experienced by breast cancers patients is the decrease of life quality of the patients. The purpose of this research was to identify factors related to the life quality of the breast cancers patients in Bandung city. This research used cross sectional method. The determination of life quality based on Quality of Life Cancer Survivor Version (QOL-CSV). Accidental sampling was used to choose samples. This research was taken place in four rumah singgah (shelters) of breast cancer located in Bandung city. There were 30 women involved in this study. Inclusive criterion in this research was the patients of breast cancers who are undergoing medications such as surgery, chemotherapy, or radiotherapy, who are willing to be the respondents voluntary. Result of normality test included age factor, marital age and firts time pregnance. Multivariate test used in this research was the linear regression analysis. Based on the result of bivariate analysis, age factor and frequency of pregnancy had positive correlated (p<0.05) to the life quality of breast cancer patients, while menarche had a negative correlated. Regression linear result was determined to life quality factor (p<0,05) including age factor, marital age and  pathology anatomy result. Half of the result of coefficient correlation showed a strong relationship in the quality of life of breast cancer patients. This Research showed that some of the reproduction factors related to the quality of life. Some factors are contributed to the quality of life of breast cancer patients such as age of the patient, marital age and result of pathology anatomy (cancer stage). This research needs more in-depths studies toward the quality of life of breast cancers patients as well as efforts of intervention to increase the quality of life of breast cancers patients.Keywords: breast cancer, quality of life, reproductive factors